2021
DOI: 10.3390/f12040412
|View full text |Cite
|
Sign up to set email alerts
|

Precommercial Thinning Increases Spruce Yields in Boreal Mixedwoods in Alberta, Canada

Abstract: A few studies in young mixedwood stands demonstrate that precommercial thinning of aspen at early ages can improve the growth of spruce and increase stand resilience to drought. However, information on tree and stand responses to thinning in older mixedwood stands is lacking. To address this need, a study was initiated in 2008 in Alberta, Canada in 14 boreal mixedwood stands (seven each at ages 17 and 22). This study investigated growth responses following thinning of aspen to five densities (0, 1000, 2500, 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 31 publications
3
10
0
Order By: Relevance
“…Early juvenile spacing of aspen generally increases the growth of residual trees (Bickerstaff 1946;Steneker 1976;Perala 1978;Rice et al 2001;Kabzems et al 2016Kabzems et al , 2022Bjelanovic et al 2021), accelerating achievement of merchantable diameter and improving the quality of the stand. Consistent with results from these other studies, thinning following spot treatments at Judy Creek resulted in a 36% increase in DBH of the 400 largest aspen per hectare.…”
Section: How Does Thinning Influence the Number And Size Of Aspen?mentioning
confidence: 99%
See 1 more Smart Citation
“…Early juvenile spacing of aspen generally increases the growth of residual trees (Bickerstaff 1946;Steneker 1976;Perala 1978;Rice et al 2001;Kabzems et al 2016Kabzems et al , 2022Bjelanovic et al 2021), accelerating achievement of merchantable diameter and improving the quality of the stand. Consistent with results from these other studies, thinning following spot treatments at Judy Creek resulted in a 36% increase in DBH of the 400 largest aspen per hectare.…”
Section: How Does Thinning Influence the Number And Size Of Aspen?mentioning
confidence: 99%
“…Several studies have demonstrated that overtopping aspen can reduce growth of understory white spruce Comeau 2007a, 2007b) and that treatments which reduce aspen densities and increase understory light levels (Filipescu and Comeau 2007a) lead to increases in spruce growth (Pitt et al 2010;Kabzems et al 2016;Bjelanovic et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…There is much empirical evidence to support the theoretical expectation that thinning maintains remaining trees that are vigorous and less prone to breakage at the individual tree level (e.g., Reukema and Bruce, 1977;Greene and Emmingham, 1986;Kim et al, 2016;Gauthier and Tremblay, 2019;Gupta et al, 2020;Bjelanovic et al, 2021). However, empirical evidence supporting the expectation of overcompensation are scares.…”
Section: Case Study 2 (Red Pine): Relative Volume Indicator Using Met...mentioning
confidence: 99%
“…Results show aspen site index ranging from 17.7 m to 26.6 m (Figure 3), with the majority of plots falling between 19 and 22 m. Three blocks were very productive (SI > 26 m). Due to a lack of measured spruce in age plots, as well as concerns about using spruce that had spent decades growing in the understory, an SI conversion model (aspen-to-white spruce) was used to calculate spruce SI [21]. Mean spruce SI varied between 14.6 m and 26.5 m across SCUP blocks, with 5 blocks having spruce SI above 23.5 m (Figure 3).…”
Section: Dataset Screening and Processingmentioning
confidence: 99%
“…In contrast, clearcutting at the culmination age of either species generally results in a loss of volume of the other species, and reductions in the total yield that could be achieved using a two-pass understory protection approach [3,4]. With proper timing of cutting, understory protection can contribute to maintaining a diversity of stand types in a mixedwood landscape, provide both spruce and aspen from the same stands, provide higher total yields [3,9,10], and reduce silviculture costs [1,3]. Grover et al (2014) [4] suggest that while harvesting and planning costs are higher, these are offset by reduced silviculture costs.…”
Section: Introductionmentioning
confidence: 99%